Effect of boron carbide on the microstructure and the mechanical properties of segments produced using hot pressing method - Islak, Serkan; Kır, Durmuş; Çelik, Ertuğrul; Çelik, Halis (Academic Journals Scientific Research and Essays Vol. 7(23), 2012)
In this study, effect of boron carbide (B4C) addition on microstructure and mechanical properties of diamond cutting segments was investigated. For this purpose, the boron carbide addition quantity was changed as 2, 5 and 10 wt%. In all of the experiments, hot pressing process was carried out at 35 MPa, at 700°C and sintering time of 3 min. Microstructure and phase composition of segments were determined by Scanning Electron Microscopy, Energy Dispersive Spectroscopy (SEM/EDS) and X-ray diffraction (XRD) analysis. Hardness and bending strength values were measured by hardness and three-point bending test devices, respectively. Hardness and bending strength values of segments changed depending on boron carbide rate.
Keywords: Segments, boron carbide, hot pressing.